ON SEVERAL STYLISTIC PROCREATIONS OF THE GHEG VARIETY OF ALBANIAN - Alma Golemi (European Scientific Journal, ESJ, 2015)
In this paper we intend to present several stylistic procreations, as expressions of various colorations, which have a certain importance in Gheg variety of Albanian and constitute an extraordinary example, not only in Ethnolinguistics, but also in shaping the features of the style of Gheg variety of Albanian, revealing as much as possible the contribution in Stylistics. Such procreations are: 1. Diminutives, with a significant importance with affectionate suffixes, such as: –ush(ë) in common nouns as: zemrush, bukurushë and proper nouns as Gjushi, Lushi. 1.2. Affectionate suffixes –losh, as: tatalosh. 1.3. New word forms, with affectionate suffixes: –z/ë (for feminine nouns) and –th (for masculine nouns): derëzën, rremtha. -lat, -llat (for plural): gjethlat; tingllat; -aç,-uc, uqe, -icë (with pejorative meaning): turulluqe, budallicë, garravaç etc. 2. Onomatopoeic words that serve as parts of a sentence: të kekllishunit; trokllimi; 3. Exclamations and elements of affirmation with exclamatory element, as: Ele; Hê; Palé, etc. Solid compound words as exclamations: Pash besën!, Pasha bukën!, Ç’â zâni lum miku? 4. Damnations and expressions of “të truarit”, as: He paç vetin n’qafë!; Mos e prûsh kryet! Such occurrences indicate a rich variety, with a particular style, with a discourse tinged with personal figurative elements, originating from areas of northern Albania.